COMPUTERIZED ACCOUNTING INFORMATION SYSTEM MANAGEMENT IN ZAM-ZAM HIJAB AR RAFI - Mulyadi Mulyadi; Dewi Rosmayanti; Mochamad Nandi Susila; Belsana Butar Butar; Hoiriah Hoiriah (Jurnal Scientia, 2023)
Advances in information technology in the modern era as it is today have a major influence in various fields, especially in the field of sales. The development of accounting information systems has led to a large number of accounting software that makes it easier to input and process accounting data in sales that have quite a lot of transaction data. Zam-zam Hijab Ar Rafi Tangerang is a business entity that needs accounting software for its sales because so far the sales system is still manual, namely only by using a mobile phone, thus allowing errors in recording and processing transaction data occur. With the implementation of Zahir Accounting Version 6.0 on Zam-zam Hijab Ar Rafi Tangerang, it can be the best solution to solve problems that exist when processing accounting data. Sales transaction data processing using Zahir Accounting Version 6.0 helps companies obtain financial reports more effectively and efficiently. Therefore, a computerized system can make company operations run better because the input time is shorter, and the financial reports produced are far more accurate than the manual method.